P132 The role of ventilation in pneumonic exacerbations of copd. (15th November 2017) - Hartley, TM; Lane, ND; Steer, J; Echevarria, C; Bourke, SC
Abstract : Introduction: In isolated pneumonia, most trials show that NIV does not improve outcome, and may delay more appropriate intubation. However in pneumonia complicating COPD with acidaemic respiratory failure (AHRF), an RCT showed NIV reduced the need for intubation and conferred a survival benefit at 2 months. 1 UK NIV guidelines state NIV is not indicated in pneumonia; whether this was intended to apply when pneumonia complicates another condition associated with a favourable response to NIV is unclear and there is substantial variation in practice. In our institution, most patients with pneumonic exacerbation of COPD (pECOPD) and AHRF receive NIV; few decline ventilation or are immediately intubated. Methods: From a consecutive historical cohort of patients receiving assisted ventilation for spirometry confirmed ECOPD and AHRF, chest radiographs, electronic data and clinical notes were reviewed. The presence of consolidation was determined in the following hierarchy: attending consultant physician interpretation (to mimic reality); radiologist report; or researcher interpretation. Analysis performed using IBM SPSS; significance identified using student's t-test, Mann Whitney U or chi-squared test for parametric, non-parametric and categorical data respectively. Results: Among patients surviving to discharge, 90 day and 6 month mortality was 12.8% and 20.3% respectively in those with consolidation, compared to 12.9% and 18.4% respectively in those without. Discussion: Compared to those without pneumonia, patients with pECOPD were older, had more comorbid illnesses, more severe acidaemia and greater functional limitation. In addition, AHRF was more likely to have developed after admission, despite initial medical therapies (an adverse prognostic marker). Unsurprisingly, in-hospital mortality was significantly higher in those with pECOPD, but approximately 2/3 survive to hospital discharge and post-discharge outcomes between the two groups are comparable. Coexistent consolidation is a marker of adverse acute outcome and an indication for closer monitoring but should not preclude ventilation, especially when so few are considered eligible for intubation. Reference: Confalonieri M, Potena A, Carbone G, et al. Acute respiratory failure in patients with severe community-acquired pneumonia: A prospective randomised evaluation of noninvasive ventilation. Am J Respir Crit Care Med1999;160:1585–91.